2019
DOI: 10.17352/gje.000009
|View full text |Cite
|
Sign up to set email alerts
|

The ecological impact on the distribution of Pangolins in Deng-Deng National Park, Eastern Region, Cameroon

Abstract: One of the major impediments to studying wild pangolins has been the diffi culty in locating them. In many areas where biodiversity surveys have been conducted, no pangolins were recorded, despite extensive nocturnal searches. The main objective of this survey was to assess the role of ecological factors on the distribution of pangolins in deng-deng national park. The research data collection method used for this study constituted the laying of fi fteen 2-kilometre transects in the study area. The collection o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
5
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(8 citation statements)
references
References 10 publications
0
5
0
Order By: Relevance
“…There are the larger questions, too, about the correlation-if not causality-between climate emergency, biodiversity loss, and the origins of the pandemic (Grandcolas & Justine, 2020;Maurice et al, 2019;Turcios-Casco & Cazzolla Gatti, 2020). There are eco-socio-political questions about whether, for instance, international flight is sustainable in the long-term (Chaudhary & Bakhshi, 2020).…”
Section: Ontology Of a Pandemic -Elizabeth Daymentioning
confidence: 99%
“…There are the larger questions, too, about the correlation-if not causality-between climate emergency, biodiversity loss, and the origins of the pandemic (Grandcolas & Justine, 2020;Maurice et al, 2019;Turcios-Casco & Cazzolla Gatti, 2020). There are eco-socio-political questions about whether, for instance, international flight is sustainable in the long-term (Chaudhary & Bakhshi, 2020).…”
Section: Ontology Of a Pandemic -Elizabeth Daymentioning
confidence: 99%
“…Similarly, pangolins are an endangered group of only 8 species that live in Asia and Sub-Saharan Africa. They are nocturnal and solitary animals in nature, they meet conspecifics only to mate and live in hollow trees or ground borrows (Maurice et al 2019). Therefore, their chances to get in contact with bats and become an intermediate host of pathogens is unlikely in nature.…”
Section: Four Urgent Actions To Conserve Wildlife and Prevent Next Pamentioning
confidence: 99%
“…Author(s) agree that this article remain permanently open access under the terms of the Creative Commons Attribution License 4.0 International License pangolins in primary and secondary tropical forests, limestone forests, bamboo forests, grasslands and agricultural fields. Similarly, Maurice et al (2019) observed that pangolins have a wide distribution, covering an array of natural and man-made habitats including tropical rain forests, subtropical thorn forests, deciduous forests, open scrublands, grasslands, cultivated lands and human settlements in Africa, unlike what was observed in India where the presence of pangolin in the pine-dominated forest was reported (Pabasara et al, 2015;Perera et al, 2017) in a comparative.…”
Section: Introductionmentioning
confidence: 95%
“…The woody plants recorded in the pangolin habitat were supported by the findings ofOdewumi and Ogunsina (2018) and were also among the important woody species recorded byOgunjemite et al (2012) in Old Oyo National Park. The habitat characteristics of the study areas are in tandem with the description ofMaurice et al (2019) that pangolin was present in various woodland and forest habitat types. Palm trees and some woody species were important to the distribution and presence of pangolin in the study areas because ants and termites are always found on the tree which provides food for the pangolin.…”
mentioning
confidence: 99%